Austrian Neutrality of 1955: A Model for Germany or the Phenomenon of the Cold War? - Alexey N. Sorokin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. The article considers the problem of solving the Austrian issue by consolidating the country’s neutrality in 1955 in the context of a possible modeling of the situation on the German issue. The consolidation of a neutral non-aligned status with Austria was the result of a broad domestic and foreign policy compromise. At the same time, the main features of the Austrian path to the neutrality of 1945–1955 are highlighted, making this one of the most well-known compromise precedents of the Cold War possible.